2017
DOI: 10.1021/acs.chemmater.7b02301
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Thermal Failure Induced by Contact between a Li1.5Al0.5Ge1.5(PO4)3 Solid Electrolyte and Li Metal in an All Solid-State Li Cell

Abstract: Chemical reactions at the solid electrolyte (SE) and Li metal interface form an interphase before electrochemical reactions occur. This study investigates the effects of the chemically formed interphase between Li metal and Li1.5Al0.5Ge1.5(PO4)3 (LAGP) on cell failures under various experimental conditions. LAGP forms a black interphase by chemically reacting with Li metal. The interphase comprises a stoichiometrically changed LAGP and Li-related oxides and behaves as a mixed ionic and electronic conductor wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
207
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(218 citation statements)
references
References 23 publications
9
207
2
Order By: Relevance
“…As shown in Figure S8a (Supporting Information), in accordance with previous reports, [11,35,36] a large total resistance was observed due to high interfacial resistances between Li metal and CS LAGP-LiTFSI. As shown in Figure S8a (Supporting Information), in accordance with previous reports, [11,35,36] a large total resistance was observed due to high interfacial resistances between Li metal and CS LAGP-LiTFSI.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As shown in Figure S8a (Supporting Information), in accordance with previous reports, [11,35,36] a large total resistance was observed due to high interfacial resistances between Li metal and CS LAGP-LiTFSI. As shown in Figure S8a (Supporting Information), in accordance with previous reports, [11,35,36] a large total resistance was observed due to high interfacial resistances between Li metal and CS LAGP-LiTFSI.…”
Section: Resultssupporting
confidence: 90%
“…As shown in Figure S8a (Supporting Information), in accordance with previous reports, [11,35,36] a large total resistance was observed due to high interfacial resistances between Li metal and CS LAGP-LiTFSI. [36] To reduce interfacial resistances, we added a small amount of liquid electrolyte (4 m lithium bis(fluorosulfonyl) imide salt (LiFSI) in 1,2-dimethoxyethane (DME) (≈5.0 µL cm −2 )) at the electrode contacts, as has been demonstrated previously to promote stable Li plating/stripping with high Coulombic efficiency (CE). [36] To reduce interfacial resistances, we added a small amount of liquid electrolyte (4 m lithium bis(fluorosulfonyl) imide salt (LiFSI) in 1,2-dimethoxyethane (DME) (≈5.0 µL cm −2 )) at the electrode contacts, as has been demonstrated previously to promote stable Li plating/stripping with high Coulombic efficiency (CE).…”
Section: Resultssupporting
confidence: 90%
“…[3] Thus, SSBs have been focused on recently and many kinds of solid electrolyte have been developed, including polymer, [4] garnet, [5] argyrodite, [6] LISICON-type, [7] NASICON-type, [8] and Perovskite-type [9] structure. [3] Thus, SSBs have been focused on recently and many kinds of solid electrolyte have been developed, including polymer, [4] garnet, [5] argyrodite, [6] LISICON-type, [7] NASICON-type, [8] and Perovskite-type [9] structure.…”
Section: Doi: 101002/aenm201801528mentioning
confidence: 99%
“…D. Rettenwander et al [61] employed Raman spectroscopy in combination with nanosecond laser-induced breakdown spectroscopy to find that the cubic-tetragonal transformation also took place in the Fe-doped LLZO. H. Chung et al [186] reported that the interphases of the Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 /Li system were composed of stoichiometrically charged LAGP with Li oxide compounds (such as Li 2 O, Li 2 O 2 , and Li 2 CO 3 with the existence of carbon at the interface). The NASICON-type LATP/LAGP SSEs also showed high reactivity toward Li.…”
Section: Origin Of the Interfacial Resistancementioning
confidence: 99%
“…2019, 9,1901810 [61,175] Raman spectroscopy; [61] In situ TEM [175] Type III LAGP Stoichiometrically charged LAGP and Li oxide compounds (Li 2 O, Li 2 O 2 and Li 2 CO 3 ) [186] XPS Type II LLTO Low-valence oxides (Ti 2 O 3 and TiO) and Ti species [178] In situ XPS Type II The type II interface should be precluded because they will make the SSEs degrade continuously, short-circuiting the batteries.…”
Section: Origin Of the Interfacial Resistancementioning
confidence: 99%